1997
DOI: 10.1128/iai.65.12.5250-5256.1997
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of antigenic determinant regions of the Bor56 protein of Orientia tsutsugamushi

Abstract: The 56-kDa protein (Bor56) of Orientia tsutsugamushi is an immunoprotective antigen and is the target molecule of neutralizing antibodies. This antigen is recognized by almost all of the serum antibodies produced by patients in the convalescence phase of scrub typhus. We expressed the Bor56 open reading frame in Escherichia coli and generated from it a series of deletion constructs as MalE fusion proteins. Antibody-binding domains were characterized by using patient sera, mouse monoclonal antibodies (MAbs), an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…56-kDa protein, which was predicted to be hydrophobic and embedded in the membrane and showed no reactivity with human IgG and IgM antibodies (23). Previous reports have shown that 56-kDa protein was always produced in the form of inclusion body in E. coli (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…56-kDa protein, which was predicted to be hydrophobic and embedded in the membrane and showed no reactivity with human IgG and IgM antibodies (23). Previous reports have shown that 56-kDa protein was always produced in the form of inclusion body in E. coli (15)(16)(17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Because the functional domain analysis of 56kDa protein was accomplished, the truncated 56‐kDa proteins were made for diagnostic tool and vaccine candidates, which were very effective. We then tried to make truncated proteins from a prior study (Seong et al. 1997b).…”
Section: Discussionmentioning
confidence: 99%
“…Although various truncated 56‐kDa proteins with deletion of both N‐ and C‐term domain differ in their infection ability, they share many structural features with other truncated 56‐kDa proteins (Ohashi et al. 1992; Seong et al. 1997a,b).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms responsible for protective immunity of O. tsutsugamushi-infected humans may involve both humoral and cell-mediated immunity (1, 2, 7-9, 13, 15-17, 20). Type-specific antigen (Tsa), a 56-kDa protein of O. tsutsugamushi, is a surface-exposed (22), major integral membrane protein (19). The immune responses to Tsa are important in preventing infection (16,17).…”
mentioning
confidence: 99%
“…The immune responses to Tsa are important in preventing infection (16,17). Animals immunized with Tsa develop both humoral and cellular immune responses to O. tsutsugamushi markedly (16,17,19). Mice immunized with recombinant Bor56, one of the Tsa, were protected from challenge with the homotype of O. tsutsugamushi (16).…”
mentioning
confidence: 99%